Pastas de obturación radicular utilizadas en tratamientos de pulpectomía en dientes deciduos. Revisión bibliográfica - Eras Díaz, Karen del Cisne (2023)
Pulpectomy treatment in deciduous teeth is a type of pulp therapy performed on deciduous teeth with necrotic pulp or irreversibly damaged pulp. Its purpose is to retain the teeth in the mouth for a longer period until the process of root resorption takes place. The objective of this research is to identify the root filling pastes used in pulpectomy treatments for deciduous teeth through a literature review. Therefore, various information sources including renowned databases such as PubMed, Scielo, ResearchGate, Medigraphic, and Google Scholar were employed. The key findings of this investigation revealed that the pastes commonly employed for root canal obturation encompass Vitapex/Metapex, zinc oxide and eugenol paste, as well as 3mix or triple antibiotic paste. In terms of clinical and radiographic success, both zinc oxide and eugenol paste and Vitapex/Metapex paste demonstrated efficacy ranging from 65% to 96% at the six- and twelvemonth follow-up periods. This literature review on root filling pastes used in pulpectomy treatments for deciduous teeth emphasizes the efficacy and clinical and radiographic characteristics of zinc oxide and eugenol paste, as well as iodophorm-based pastes (Vitapex/Metapex). These findings provide valuable information for the selection and evaluation of root filling pastes in pulpectomy procedures